POTENSI TRANSDIFERENSIASI SEL FIBROBLAS MENJADI SEL SARAF SECARA IN VITRO (Transdifferentiation Potency of Fibroblast Cell to Neuron Cell in Vitro) - Ekayanti M. Kaiin; Ita Djuwita (Jurnal Kedokteran Hewan, 2016)
The aim of this study was to examine the potency of fibroblast cells transdifferentiated to neuron cells in vitro. Newborn rat neuron conditioned medium (NBRN CM) was collected from neuron cells cultured with mDMEM without serum for 48 hours. Fibroblast cells were collected from fetal rat muscle treated with trypsin. Fibroblast cells were culture with 3 kind of culture medium: mDMEM + 0.01 mM          β-mercaptoethanol; mDMEM + 50% NBRN-CM and  mDMEM + 0.01 mM β-mercaptoethanol + 50% NBRN CM . As control, cells was cultured with mDMEM +10% newborn calf serum (NBCS). The addition of NBRN CM into culture medium resulted in 12.97% newborn cells in fibroblast culture medium passage I. Newborn rat neuron conditioned medium in fibroblast culture medium resulted 12.97% neuron cells at passage 1. The percentage was increased (14.60%) when β- mercaptoethanol added into medium. The same result was found at passage 3 (12.67%; 13.17%). It showed that fibroblast cells has potency to transdifferentiated into neuron cells when cultured with NBRN CM. Further research is needed to know the fibroblast transdifferentiation potency. Key words: fibroblast, transdifferentiation, conditioned medium, neuron cells, in vitro